Management of root rot disease of fenugreek - S S Rao, A K Singh, (Journal of Spices and Aromatic Crops, 2015)
Field experiments were conducted for two years for the management of root rot of fenugreek and it was found that maximum reduction in disease incidence (14.52% and 11.4%, respectively) was observed in the treatment where seeds were treated with carbendazim (2 g kg-1) + spray at 45, 60 & 75 days after sowing during both the years. This treatment also registered maximum seed yield of 7.3 q ha-1 and 7.9 q ha-1, respectively during the two years. The next best treatment was seed treatment with hexaconazole (2 mL kg-1) + spray (0.2%) at 45, 60 & 75 DAS with disease incidence of 16.41% and 13.7%, respectively and yield of 6.8 and 7.5 q ha-1, respectively.